Dynamic Iminoboronate‐Based Boroxine Chemistry for the Design of Ambient Humidity‐Sensitive Self‐Healing Polymers - Delpierre, Sébastien; Willocq, Bertrand; De Winter, Julien; Dubois, Philippe; Gerbaux, Pascal; Raquez, Jean‐Marie (Chemistry : a European journal, 2017)
Developing intrinsic self‐healing polymeric materials is of great interest nowadays to extend material lifetime and/or prevent the replacement of damaged pieces. Spontaneously humidity‐sensitive healable polymer network built around dynamic covalent B−O bonds was templated by using iminoboronate‐based boroxine derivatives. Taking advantage of the dynamic boroxine/boronic acid equilibrium and iminoboronate chemistry, it is possible to construct polymeric materials able to self‐heal without requiring any energy‐demanding external activation. Interestingly, this novel family of iminoboronate adduct‐based materials can be readily produced by a relatively simple and straightforward synthesis between boronic acid and diamine‐based compounds, paving the way to coatings that are self‐healable at ambient humidity. A healing power: The design of a polymeric material displaying intrinsic self‐healing properties without the requirement of energy‐demanding external activation has been achieved by bringing together a boroxine/boronic acid equilibrium and iminoboronate chemistry. Spontaneously, a humidity‐sensitive healable polymer network built around the dynamic covalent B−O bonds was thereby created by using a iminoboronate‐based boroxine moiety as a crosslinking node.